Peran Guru Bahasa Indonesia dalam Membentuk Karakter Siswa yang Berintegritas - Dipayana, I Ketut; Sudarsana, I Ketut; Dewi, Ni Putu Candra Prastya (GERAM, 2025)
Character education is a fundamental pillar in shaping a generation that excels not only intellectually but also possesses strong moral integrity. Although national policy has emphasized the importance of character reinforcement through the curriculum, its implementation in the classroom—particularly in subjects considered technical, such as Indonesian language—remains suboptimal. There is a gap between the potential of Indonesian language instruction as a medium for character education and its current practice, which still predominantly focuses on linguistic aspects. This study aims to describe the role of Indonesian language teachers in shaping students' character, particularly the value of integrity. A descriptive qualitative approach was employed, using data collection techniques including in-depth interviews, classroom observations, and document analysis. The research was conducted in two secondary schools involving both teachers and students as participants. The findings reveal that Indonesian language teachers play a strategic role in internalizing the value of integrity through various strategies, such as the selection of morally rich texts, implementation of reflective literacy projects, and attitude-based assessments. The teacher’s role as a moral role model and the interpersonal relationships developed in the classroom also significantly contribute to the internalization process. However, this role has not been fully optimized due to structural barriers, including administrative burdens, lack of training in character-based pedagogy, and the dominance of academic-oriented curricula. The study concludes that Indonesian language teachers have considerable potential as agents of character education—potential that remains underutilized. The practical implication of these findings is the need for systemic support, including ongoing training in value-based pedagogy, supportive curriculum policies, and the reduction of administrative workloads to enable teachers to effectively and sustainably fulfill this strategic role.